A mapping of the kinds of work activities and other productive uses inspired by play or games - StÃ©phane Goria (Bina Nusantara University, 2022)
This paper is about a theoretical study consisting in listing and positioning different kinds of serious uses derived or inspired by play or games. Indeed, since the beginning of the 2000s, the number of these forms has increased exponentially and it is becoming very complicated to find one's way through. In our opinion, there is currently a problem of distinction between the various serious forms derived or inspired by the practice of a playing activity and the design of a game structure. In this article, we try to bring a beginning of answer to this problem. To do this, we began by exploring the scientific literature dealing with these different forms. We started with the reference works that we reconsidered from this large variety of forms. Subsequently, we explored possible categorizations based on a limited number of variables. We were then able to draw two diagrams: one to represent graphically the categories identified according to the chosen variables, and another to present 6 combinable design process that can be followed to create any of these serious game or play categories.